Reynolds number effects in the flow of a Vočadlo electrorheological fluid in a curved gap - Walicka, Anna; Falicki, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
Many electrorheological fluids (ERFs) as fluids with micro-structure demonstrate a non-Newtonian behaviour. Rheometric measurements indicate that some flows of these fluids may by modelled as the flows of a Vočadlo ER fluid. In this paper, the flow of a Vočadlo fluid - with a fractional index of non-linearity - in a narrow gap between two fixed surfaces of revolution with a common axis of symmetry is considered.
Keywords: inertia effects; fixed surfaces of revolution; Vočadlo ER fluid; pressurized flow